The agreement between physical activity time reported by the IPAQ and accelerometer in postmenopausal women - Rosa, Clara Suemi Costa [UNESP]; Rossi, Fabrício Eduardo [UNESP]; Buonani, Camila [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Monteiro, Henrique Luiz [UNESP]; Junior Freitas, Ismael Forte [UNESP] (Desafio Singular, Lda, 2015)
The objective of this study was to assess, in a sample composed by postmenopausal women, the agree-ment between physical activity time reported by short version of the IPAQ and measured by accelerom-eter in different intensities. The participants consisted of postmenopausal women aged ≥ 50 years (N = 60, mean age 61.5±7.5 years). They completed the IPAQ (short version) and then wore an accelerom-eter for one week. Statistical analysis was composed by the Kappa index, McNemar's test, specificity and sensitivity, Spearman's rank correlation and the Wilcoxon test. The amount of time spent in moderate and vigorous physical activity had weak correlation (r=-0.04-0.28) between accelerometer and IPAQ. IPAQ overestimated the minutes spent in moderate and vigorous intensities and underestimated the time spent in light activities. There was not significant agreement between instruments (kappa index= 0.151±0.111; p= 0.185; sensibility, 46% and specificity, 28%). There was a significant inconsistence for the time of physical activity reported by IPAQ.
Keywords: Accelerometer; Aging; Agreement; Menopausal; Questionnaire